Vitamin D Supplementation and Allergic Rhinitis: A Systematic Review and Meta-Analysis - Kei Kawada; Chiemi Sato; Tomoaki Ishida; Yui Nagao; Takaaki Yamamoto; Kohei Jobu; Yukihiro Hamada; Yuki Izawa Ishizawa; Keisuke Ishizawa; Shinji Abe (Medicina)
Background and Objectives: Vitamin D supplementation is effective for allergic rhinitis; however, its usefulness is unclear. We conducted a systematic review and meta-analysis to examine the conditions in which vitamin D supplementation was effective in allergic rhinitis management. Materials and Methods: Randomized controlled trials of vitamin D supplementation used for patients with allergic rhinitis were searched for across different databases. We extracted scores on patients’ symptoms and the medication types used as the baseline treatments and performed a meta-analysis to evaluate the effect of vitamin D supplementation on allergic rhinitis symptoms. Meta-regression and subgroup analyses were performed for the average age, proportion of female participants, concomitant medications, vitamin D administration durations, and baseline serum 25-hydroxyvitamin D levels. Results: In total, 2389 articles were screened, and 5 randomized controlled trials (RCTs) were included in the meta-analysis. Compared with placebos, vitamin D supplementation alleviated allergic rhinitis symptoms, although the difference was not significant; there was significant heterogeneity among studies (standardized mean difference [SMD] = −2.69, 95% confidence interval [CI]: −6.20 to 0.82, I2 = 98%, p < 0.01). The proportion of female participants in the RCTs (slope: 0.21, p = 0.026) and concomitant corticosteroid use (slope: −9.16, p = 0.005) influenced the vitamin D response. Compared with the placebos, vitamin D supplementation without corticosteroids alleviated the allergic rhinitis symptoms (SMD = −0.56, 95% CI: −0.90 to −0.23). Combination treatment with corticosteroids also non-significantly alleviated symptoms. Additionally, the heterogeneity between studies was significant (SMD = −5.97, 95% CI: −13.55 to 1.16, I2 = 99%, p < 0.01). Conclusions: The study results suggest that vitamin D supplementation alleviates allergic rhinitis symptoms, although the effects differ according to the patient’s sex and concomitant medications.